Characterization of SiO2-TiO2 and Photocatalytic Degradation of Methyl Orange - Zhou, Lina; Han, Xiaofang; Zhang, Wenjie; He, Hongbo (Asian Journal of Chemistry, 2014)
A SiO2-TiO2 composite photocatalyst was prepared through sol-gel method for photocatalytic degradation of methyl orange. The material is composed of anatase TiO2 and most probably amorphous SiO2. The crystallite size of the TiO2 (101) plane is 14.39 nm. The surface of the sample is fairly rough. Some particles in the size smaller than 1000 nm scatter on the surface. The pore size of the material is mainly below 15 nm and the pore diameter mainly distributes in the range from 2 nm to 11 nm. Adsorption only contributes a small part, less than 1.36 %, to the total decoloration of methyl orange on the TiO2-SiO2 material. The degradation of methyl orange continues with increasing irradiation time. Degradation rates after 0.5 and 2 h are 31.1 % and 92.9 %. The two main absorption peaks of methyl orange at 468 nm and 270 nm decline with increasing reaction time.